2014
DOI: 10.1017/s0007114514000890
|View full text |Cite
|
Sign up to set email alerts
|

Dietary grape powder increases IL-1β and IL-6 production by lipopolysaccharide-activated monocytes and reduces plasma concentrations of large LDL and large LDL-cholesterol particles in obese humans

Abstract: Obese individuals are at an increased risk of developing CVD, hypertension, type 2 diabetes, and bacterial and viral infections when compared with the normal-weight population. In a 9-week randomised, double-blind, cross-over study, twenty-four obese subjects aged between 20 and 60 years and with a BMI between 30 and 45 kg/m 2 were fed grape or placebo powder for 3-week intervals to determine the effects of dietary grapes on blood lipid profiles, plasma inflammatory marker concentrations and immune cell functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 45 publications
(42 reference statements)
1
70
1
1
Order By: Relevance
“…47 In this study, dietary grape powder supplementation (46 g grape powder in 240 mL of water, two times per day for 3 weeks, representing four servings of grapes/day) was found to (1) reduce plasma concentrations of large LDL cholesterol and large LDL particles, and (2) increase production of IL-1β and IL-6 in supernatants from lipopolysaccharide-activated peripheral blood mononuclear cells (PBMCs). 47 …”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 92%
“…47 In this study, dietary grape powder supplementation (46 g grape powder in 240 mL of water, two times per day for 3 weeks, representing four servings of grapes/day) was found to (1) reduce plasma concentrations of large LDL cholesterol and large LDL particles, and (2) increase production of IL-1β and IL-6 in supernatants from lipopolysaccharide-activated peripheral blood mononuclear cells (PBMCs). 47 …”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 92%
“…A similar effect on FMD was observed in adolescents affected by metabolic syndrome [12] and in adults with coronary artery disease [19]. The investigators suggested that the observed effects were due to the enhancement in the nitric oxide (NO) bioactivity, responsible for the positive modulation of endothelial function.…”
Section: Resultsmentioning
confidence: 67%
“…The investigators suggested that the observed effects were due to the enhancement in the nitric oxide (NO) bioactivity, responsible for the positive modulation of endothelial function. Controversial results were observed on the improvement of plasma cholesterol profile (reduction of LDL-cholesterol mediated by an increased expression of LDL receptors) after the intake of grape derivatives (4 studies in favour and 4 without significant difference) [13,15,19,20], while significant …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While no effect was seen in this combined population, investigations of subpopulations and more sophisticated analysis of lipids has been carried out in other studies. One study found that plasma concentrations of large LDL-C and large LDL particles compared with placebo were decreased in obese subjects supplemented with grape powder for 3 weeks (30). However, the most atherogenic small LDL particles were not affected by treatment (85).…”
Section: Polyphenolsmentioning
confidence: 99%